In vitro larval rearing protocol for the stingless bee species Melipona scutellaris for toxicological studies - Dorigo, Adna Suelen [UNESP]; de Souza Rosa-Fontana, Annelise [UNESP]; Soares-Lima, Hellen Maria [UNESP]; Galaschi-Teixeira, Juliana Stephanie; Nocelli, Roberta Cornélio Ferreira; Malaspina, Osmar [UNESP] (Public Library of Science (PLoS), 2019)
Brazil has the highest biodiversity of native stingless bees in the world. However, Brazilian regulations are based on protocols standardized by the Organization for Economic Cooperation and Development (OECD), which uses Apis mellifera as a model organism. The safety of the use of an exotic species as a substitute for a native species is a problem that concerns members of the academy and the government agencies responsible for studies of this nature in the neotropical regions where there are occurrences of stingless bee species. Regarding the exposure of larvae to pesticides, several indicators suggest that the same rearing method for A. mellifera cannot be applied to stingless bees, mainly because of their different feeding systems. Thus, it is necessary to establish an in vitro rearing method for native social bees. We developed a larval rearing method for the stingless bee species Melipona scutellaris and evaluated parameters such as the defecation rate, pupation, emergence, mortality and morphometry of the newly emerged workers. The control was represented by the morphometry of individuals that emerged from natural combs (in vivo). In addition, we determined the average lethal concentration (LC 50 ) of the insecticide dimethoate, the standard active ingredient used for the validation of toxicity tests. Procedures conducted prior to the in vitro bioassays allowed us to obtain the actual dimensions of the rearing cells for making acrylic plates for use in establishing how much each larva consumes during its development, that is, determining how much larval food should be placed in every artificial cell. Tests performed with M. scutellaris indicated an average of 80.2% emergence of individuals relative to the larvae, 92.61% relative to the pupae and a mean of 7.42% larval mortality. The mean of the intertegular distance, head width and wing asymmetry parameters were not significantly different between individuals from the in vitro and in vivo rearing methods. The LC 50 value determined was 27.48 ng dimethoate / μL diet. The method described for M. scutellaris showed development rates above OECD standards, which requires at least 75% emergence, and produced newly emerged workers with similar dimensions to those produced under natural conditions; thus these results enable their use as a rearing protocol for this species (or genus) and, consequently, their use in toxicity tests. The results produced with M. scutellaris are the first steps for a proposed toxicity test protocol for stingless bee larvae that can be standardized and included as a protocol in the OECD.